Contributions for standardisation of plate loading test - Martins, João Paulo (2008)
One of the objectives of this work was the interpretation of results of plate loading tests following standards AFNOR NF P94-117-1 (plate of 600 mm) and DIN 18134 (plate of 300 mm) and the comparison between them, in order to develop a specification of this test to be used as a reference method in Portugal by REFER.